FINANCIAL PERFORMANCE OF ISLAMIC BANKING IN INDONESIA WITH MAQASID SHARIAH APPROACH - Rahmat Hidayat; Yeni Oktaviani; Aminudin Aminudin (Manajemen Bisnis, 2019)
This research aims to demonstrate the financial performance of Islamic banking in Indonesia using the Maqasid al-Shariah approach. This study used Partial Least Square (PLS) to evaluate the relationship between the Maqasid al-Shariah concept and its indicators and linear regression to prove causality relationship between variables. The research objects were Bank Muamalat Indonesia (BMI), Bank BRI Syariah (BRIS), Bank BNI Syariah (BNIS), Bank Mandiri Syariah (BMS), Bank Panin Syariah (PBS), and Bank Mega Syariah Indonesia (BSMI). The results demonstrated that the indicator of research and development were the dominant indicators in the aspect of Tahdhib al-Fard (Individual Education) and had a contribution to ROE. However, the Tahdhib al-Fard aspect (Individual Education) did not affect ROA. The indicator of equitable development was the dominant indicator in the aspect of Iqamat al-Adl (building justice) and did not affect ROA; however, equitable and functional distribution of murabaha and musyarakah contributed to ROE. The indicator of real sector investment in the aspect of Jalb al-Maslahah (improving welfare) had a dominant formative contribution, and it contributed to ROE. The concept of Maqashid Shariah simultaneously affects 34.9% of ROA and 39.7% of ROE.